Epidemiological study of legionellosis in Spain. Year 2022 (Boletín Epidemiológico Semanal, 2023)
Introduction: Legionellosis is a disease of environmental origin transmitted by aerosols of water contaminated with L. pneumophila. Legislation for the control of risk facilities and surveillance to early detection of outbreaks are key in their control. We carried out and display the analysis of legionellosis cases notified to the National Epidemiological Surveillance Network (RENAVE).Method: Descriptive epidemiological analysis of legionellosis cases notified in 2022 in Spain. Information from the European network for surveillance of cases associated with travel are also analysed.Results: 1,992 cases were reported, of which 1,959 were autochthonous (TN=4.11). There was a 43.1% increase over the cases in 2021. 1,360 cases were reported in men (TN=5.83, median age 65) and 592 in women (TN=2.44, median age 70) and in seven cases this information was unknown. The highest rates occurred in the age groups 45-64 and 65-84, both for men and women. The case fatality ratio (CFR) was 6.2% (122/1,959) and increased with age. Was 5.6% (76/1,360) in men and 7.8 in women (46/592).Conclusions: The trend in the number of cases of the disease is increasing. The disease affected more men than women, the elderly and those with risk factors such as smoking or immunosuppression. In addition, for men, the incidence was high in the active stage of life, probably related to some professions or jobs.
Keywords: Legionellosis; Legionella pneumophila; epidemiological surveillance